Leveraging Generative Artificial Intelligence to Enhance the Quality of Adaptive Learning at the Junior High School Level in Surakarta City - Winarno; Heri Prasetyo; Wiranto; Sari Widya Sihwi; Herdito Ibnu Dewangkoro; Tarno; Anik Indriyani (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT The primary and secondary education curriculum in Indonesia changes almost every year. These changes lead to administrative adjustments in teaching and learning documents. Consequently, teachers tend to spend less time focusing on delivering instructional content and ensuring meaningful student learning, and instead devote substantial effort to reformatting lesson plans (RPP), student activity reports (LKPD), and other administrative documents. In many cases, these documents remain largely unchanged from year to year, with minimal innovation. To address this issue, a more efficient approach is required to enable teachers to innovate in designing instructional materials, lesson plans, student worksheets, and assessment instruments. The aim of this community engagement initiative is to enhance pedagogical and digital literacy in the use of generative AI to assist teachers in drafting learning objectives, structuring classroom activities, generating guiding questions, developing variations in instructional strategies, and producing effective teaching materials tailored to students’ needs. This activity was implemented using the ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation). The results indicate that participants demonstrated a strong understanding of the material and an improvement in their cognitive knowledge. Specifically, 41.67% of participants reported that the material was easy to understand, while 58.33% stated that it was very easy to understand. Furthermore, 75% of participants indicated that the facilitator delivered the material very well, and 25% rated the delivery as good. A recommendation for future initiatives is the need for ongoing support through a post-training mentoring programme to ensure an understanding of the ethical use of generative AI. Keywords: generative AI, education, prompt, adaptif learning.